46 Primary Care Practitioners Have A High Level of Satisfaction with The Current Breast Referral Pathway but The Majority Would Support A Change to Patient Self-Referral. (12th October 2021) - Russell, T; Cooper, J; McIntyre, M; Ramzi, S
Abstract: Aim: Currently, patients must consult with a primary care practitioner (PCP) prior to being referred to secondary care breast services. A change to patient self-referral would arguably reduce primary care workload, improve access for patients, and allow breast units to allocate resources more appropriately; no data currently supports this. This study aims to explore PCP's views on breast referral, evaluate the community breast workload, and to investigate the impact of COVID-19 on referral rates. Method: An electronic survey was designed on SurveyMonkey.com which aimed to collect both quantitative and qualitative data. The weblink to the survey was sent out via two electronic newsletters. Participants were asked: their role and gender, their level of confidence surrounding breast care, details surrounding their breast workload, how they felt COVID-19 had affected their referral rates, their level of satisfaction with the current pathway, and their opinions on a potential change to patient self-referral. Results: 79 responses were received. PCPs estimated that 7.0% (median) of their total consultations were regarding a breast-related issue and that COVID-19 had not had a significant impact on the rate of referral to breast units (P = 0.75). 84.8% of PCPs were satisfied with the current referral pathway. Whilst 74.5% felt a change to patient self-referral would benefit patients and primary care services, their free text comments highlighted some of their reservations. Conclusions: PCPs have a high level of satisfaction with the current breast referral pathway, but the majority would be open to a change to patient self-referral to specialist breast units.